THE EFFECT OF THE USE OF NIPA PALM (Nypa fruticans) EXTRACTSON CHANGES IN SENSORY AND MICROBIOLOGY QUALITY OF FRESH NILE TILAPIA (Oreochromis niloticus) FILLETS DURING COLD STORAGE (± 5 °C) - Debi Rachmadani; Syahrul Syahrul; Bustari Hasan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstrak This research was aimed to determine the effect of the use of nipa palm (Nypa fruticans) extracts on changes in sensory and microbiology quality of fresh nile tilapia fillets during cold storage (± 5 °C). This research was carried out in two stages, namely the preliminary research and primary research. Preliminary research was conducted to find out the best concentration and long immersion based on sensory test. Nipa palm extract concentration used was 5% (K5), 10% (K10) and 15% (K15) and soaking time for 30 (M30) and 60 (M60) minutes. Primary research was the advanced research to determine the durability of niletilapia fillets soaked in the best concentration and immersion time with sensory and microbiological parameters. The design used was non factorial Randomized Completely Block Designwith long cold storage for 20 days and observed for 0, 4, 8, 12, 16, 20 days. The preliminary results showed that the best treatments were K5M30 and K10M30 based on sensory test. During cold storage based on sensory quality with border line 5 that K5M30 and K10M30treatments can be accepted until the 12th days although microbiological quality on 20th days of cold storagestill accepted for TPC parameter, while the Staphylococcus aureus parameters can only be maintained until the 16th days and Salmonella sp. and E. coli was negative on the level of treatment. Keywords:Nipa palm Extract, antibacterial, fish fillet,cold storage,quality